2017
DOI: 10.1377/hlthaff.2017.0173
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Veterans’ Hospice Use: The Veterans Health Administration’s Focus On Improving End-Of-Life Care

Abstract: In 2009 the Department of Veterans Affairs (VA) began a major, four-year investment in improving the quality of end-of-life care. The Comprehensive End of Life Care Initiative increased the numbers of VA medical center inpatient hospice units and palliative care staff members as well as the amount of palliative care training, quality monitoring, and community outreach. We divided male veterans ages sixty-six and older into categories based on their use of the VA and Medicare and examined whether the increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…8,9 Indeed, Medicare-enrolled veterans are more likely to use hospice than are general Medicare beneficiaries. 24 This VA policy enables the concurrent receipt of hospice care and disease-modifying treatment, and the present study suggests that as hospice use increased, there was an associated increase in the concurrent receipt of radiation therapy and chemotherapy and hospice care. 2 Consistent with our finding of greater concurrent care among veterans in high HEQs, we found that nearly 75% of patients with newly diagnosed stage IV NSCLC received chemo-therapy in the first 6 months after diagnosis or until death, but even in the highest HEQ VAMCs, only 6% of patients received chemotherapy after hospice initiation.…”
Section: Discussionsupporting
confidence: 51%
“…8,9 Indeed, Medicare-enrolled veterans are more likely to use hospice than are general Medicare beneficiaries. 24 This VA policy enables the concurrent receipt of hospice care and disease-modifying treatment, and the present study suggests that as hospice use increased, there was an associated increase in the concurrent receipt of radiation therapy and chemotherapy and hospice care. 2 Consistent with our finding of greater concurrent care among veterans in high HEQs, we found that nearly 75% of patients with newly diagnosed stage IV NSCLC received chemo-therapy in the first 6 months after diagnosis or until death, but even in the highest HEQ VAMCs, only 6% of patients received chemotherapy after hospice initiation.…”
Section: Discussionsupporting
confidence: 51%
“…While some medical centers established dedicated hospice/palliative care wards in acute care facilities, CLCs became the locus of hospice and palliative care in the majority of VA medical centers. An article recently published by Miller et al (2017) found that male Veterans aged 66 and older had increases in their rates of hospice use within the last year of life following the CELC initiative. Therefore, the findings from these two studies, taken together, suggest that the CELC initiative was successful in increasing the number of Veterans who had access to hospice services.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that rural residents were less likely than urban residents to die in an inpatient hospice unit is similar to findings on overall hospice use outside of the VA. 4,5,7,8 However, it is important to note that veterans who died while receiving hospice care at home or in non-VA settings-freestanding hospice units, other hospitals, or facilities-were not included in our study. 48 Our study adds to previous research by identifying a similar trend in a clinically diverse population and examining death in an inpatient hospice unit as an indicator across multiple inpatient settings. Comparing odds ratios between rural categories, our findings depart from previous research outside the VA, which found that isolated and remote rural residents were the least likely of all to use the service.…”
Section: Discussionmentioning
confidence: 76%